A Two-Stage Model of Diversion Knowledge and Skills Highlights Where Pilot Factors Impact Safety-Related Outcomes. Issue 4 (2nd October 2021) - Van Benthem, Kathleen; Herdman, Chris M.
ABSTRACT: Objective : To assist stakeholders apply targeted safety strategies, we developed and tested a two-stage model of diversion knowledge and skills. Background : Understanding pilot factors in weather-related diversions is integral to reducing the phenomenon of visual flight rules flight into meteorological conditions. Method : Thirty-six general aviation pilots flew a cross-country flight in a Cessna 172 simulator where they encountered an ATC-directed diversion due to deteriorating weather. Path analyses quantified effects in a two-stage model based on criteria specified by aviation regulations. Results : In stage 1, low cognitive flexibility and fewer recent pilot-in-command hours were associated with greater likelihood of ignoring the diversion instruction. Low cognitive flexibility was also associated with errors in locating the alternate aerodrome and incorrect procedures at the alternate. At stage 2, there were significant positive paths from a diversion efficiency variable to all aspects of pilotage. Pilotage positively predicted awareness of ownship and traffic, and was associated with fewer altitude violations. Conclusion : We provide empirical evidence for the association between the cognitive factors related to continuation bias and high-risk responses to diversion instructions. Using a two-stage model to conceptualize pilot performance illuminates the impact of cognitive factors in weather-related diversions. Highlighting the pivotal human factors at two clear junctions of an unexpected diversion can more fully prepare pilots to safely manage these risk-laden events.